Penentuan Fasies Sentral Gunung Api Purba Menggunakan Metode Gravitasi Pada Kawasan Gunung Ijo, Pegunungan Kulonprogo - Nuzula, Jannatul Firdausi; Setiahadiwibowo, Ajimas Pascaning (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2023)
The Kulon Progo Mountains are a range of Old Volcanoes that are no longer active so that the body is difficult to identify as a volcano body. One of the old volcanoes in the Kulon Progo Mountains is Mount Ijo. The description of the subsurface through the characteristics of the existence of ancient volcanoes uses a geophysical method approach, namely the gravity method with supporting data in the form of geological studies of the Mount Ijo area. This is done to get the distribution of variations in the subsurface gravity field of Mount Ijo. The gravity data used is GGMPlus gravity satellite data with a lot area of 8.32 x 14.23 Km with a point distribution of 2368 points. In the processing process, a derivative analysis is carried out using Total Horizontal Derivative (THD) and Total Derivative (TDR). The results obtained from the ABL value of the Mount Ijo area illustrate the distribution of gravity anomaly values with high values ranging from 0.2 mGal to 3.5 mGal in the center of the map indicating the presence of the peak of Mount Ijo which is the central facies of Mount Ijo. Supported by the presence of structures in the form of faults and intrusion hills included in the proximal facies surrounding the central facies.  The 2.5-dimensional model of the 2 incisions of the residual anomaly map has a depth of 800m and produced a picture of the central facies, proximal facies and a small part of the medial facies of Mount Ijo.